Menopause, anti-Müllerian hormone and cognition in a cohort of women with persistent symptoms following TBI: a case for future research. (3rd July 2021) - Biscardi, Melissa; Shafi, Reema; Cullen, Nora; Einstein, Gillian; Colantonio, Angela
ABSTRACT: Objectives : Primary: To explore anti-Müllerian Hormone (AMH) levels in community dwelling women following TBI. Secondary: To explore the relation of AMH to menstrual cycle, cognition, distress and symptoms of menopause. Setting: Large adult TBI outpatient clinic in Toronto Canada. Research design: Prospective study of 10 women with persistent symptoms who were one or more years post TBI. Methods: Consenting participants provided a serum sample for AMH levels, and completed the Menopause Rating Scale (MRS), Symptom Checklist-90 r (SCL-90 r), Repeatable Battery for the Assessment of Neurological Status (RBANS) and a health questionnaire. Main outcomes and results: This study found lower than expected levels of AMH in 50% of participants relative to age matched norms and 50% of participants experienced new onset of menstrual changes. Also notable were findings of lower-than-expected cognitive scores in women over 35 and reports of menopause-related symptoms across all ages groups. Conclusions: As our understanding of the role of AMH grows, examining changes in this novel biomarker in the long-term post-TBI is warranted. Future research should be sufficiently powered to expand on and validate the study's findings.